The convergence of laws : a typology of implementation models and factors - Platsas, Antonios Emmanuel (Trinity College (Dublin, Ireland). School of Law, 2007)
This thesis is divided into five parts and eight chapters. In the first part of the thesis one finds Chapters 1 and 2, which are purely introductory. In the second part one finds the models proposed, within Chapters 3 and 4. In the third part the proposed factors are to be found, within Chapters 5 and 6. In the fourth part of the thesis the academic input through interviews is to be found, in Chapter 7. In the final and fifth part, one finds the concluding Chapter 8. In particular: Chapter 1 sets out the thesis, its objectives and its aims of this thesis and provides the chronology of analysis. Chapter 2 sets out the parameters for the four models and factors of law implementation, which follow this chapter. It also incorporates the necessary background m aterial which will acquaint the reader with the notion of law convergence and the surrounding material thereto, as well as other material in relation to the rest of the thesis. Chapter 3 proposes the first model of implementation of convergent law, the 'general model of implementation'. Chapter 4 proposes the second model of implementation of convergent law, the 'specific/restructuring of implementation'. Chapter 5 proposes the third factor of implementation, the 'comparative law factor of implementation'. Chapter 6 proposes the fourth and final factor of implementation of convergent law, the 'socio-legal factor of implementation'. Chapter 7 examines qualitatively the answers of thirty-three academic law experts from Europe and the world on the question of convergence and other surrounding questions to this thesis. Chapter 8 incorporates the conclusions of this thesis.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin